PERAN WORK FAMILY CONFLICT MEMEDIASI ROLE STRESS TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN - Pradnyana, I Kadek Wiweka; Sudharma, I Nyoman (E-Jurnal Manajemen; Vol 5 No 8 (2016), 2016)
The purpose of this study was to determine the role of work family conflict mediating role of stress on organizational commitment of employees at PT. Tjendana Mandra Sakti Denpasar. This research was conducted at PT. Tjendana Mandra Denpasar Sakti engaged in the services of tour and travel with the technique of path analysis (path analysis). The number of samples, by using census method (total sampling) is as much as 118 respondents. Based on the results of the analysis showed that role stress positive and significant effect partially on work family conflict. role stress negative and significant effect partially to organisasioanal commitment. Work family conflict significantly mediates the negative effects of stress on the role of organizational commitment of employees at PT. Tjendana Mandra Sakti Denpasar.
Keywords: Role of Stress, Work Family Conflict, Organizational Commitment